Mental Health Impacts of Using Social Media Among University of Halabja Students (Kurdistan Region of Iraq) - Noori, Razaw; Hussein, Hataw Hama Saleh; Ibrahim, Aweza (ANFUSINA: Journal of Psychology, 2022)
In the recent years, the use of social media has increased. Social media is the fastest way to reach information and make online communication. According to worldwide digital population- Internet - Statista on Jul 26, 2022, there are five billion internet users worldwide, which means 63 percent of the population in the world. This data further indicates that the male’s use of social media was higher than females. The Kurdish version of Hopkins Symptoms CheckList -25 and Perceived Stress Scale was used to assess psychological distress among university students that used social media. The questionnaire was distributed randomly among university students. Finally, 143 university students participated in the study. The prevalence of depression and anxiety was 65.03%, 62.24%, the level of stress was (M = 17.77, SD = 5.570). As a result, high levels of depression, anxiety, and stress among both females than males Halabja University students were found.  This study aimed to indicate the impacts of social media on mental health among Halabja University students. The study found out that the use of social media has been making negative impacts on students’ mental health.